The Role of Satisfaction with Life and Fear of Missing Out as Predictors of Problematic Social Media Use and Problematic Smartphone Use Among Generation Z - Syifa Fauziah Hamidah; Lindi Utami Marquerette; Roro Arinda Reswanti Julian Pratama (Almana : Jurnal Manajemen dan Bisnis, 2026)
The rapid growth of social commerce platforms, particularly TikTok Shop, has increased the intensity of social media and smartphone use among Generation Z, which may lead to problematic patterns of digital behavior. This study aims to examine the role of satisfaction with life and fear of missing out (FOMO) as predictors of problematic social media use and problematic smartphone use among Generation Z TikTok Shop users. This research employs a quantitative approach using a survey method involving Generation Z respondents who actively use TikTok Shop. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that satisfaction with life has a significant effect on problematic social media use and problematic smartphone use, while fear of missing out (FOMO) is also found to have a significant effect on both forms of problematic digital behavior. These findings suggest that individual psychological well-being and digital motivational factors play an important role in shaping the intensity and patterns of social media and smartphone use among Generation Z. This study contributes theoretically to the understanding of psychological factors influencing problematic digital behavior and provides practical implications for enhancing digital well-being among social commerce platform users.